2014
DOI: 10.1155/2014/783059
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Blackcurrant Extracts (Ribes nigrumL.) in Relation to Erythrocyte Membranes

Abstract: Compounds contained in fruits and leaves of blackcurrant (Ribes nigrum L.) are known as agents acting preventively and therapeutically on the organism. The HPLC analysis showed they are rich in polyphenol anthocyanins in fruits and flavonoids in leaves, that have antioxidant activity and are beneficial for health. The aim of the research was to determine the effect of blackcurrant fruit and leaf extracts on the physical properties of the erythrocyte membranes and assess their antioxidant properties. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 56 publications
1
22
0
3
Order By: Relevance
“…Some studies demonstrated that UVC radiation changes erythrocyte membrane (31). Disturbance of the membrane causes penetration of lytic component and collection of water into the cell lead to hemolysis (31). A similar result was seen in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some studies demonstrated that UVC radiation changes erythrocyte membrane (31). Disturbance of the membrane causes penetration of lytic component and collection of water into the cell lead to hemolysis (31). A similar result was seen in our study.…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted by Kaestner et al also showed that UV radiation leads to hemolysis of RBCs (30). Some studies demonstrated that UVC radiation changes erythrocyte membrane (31). Disturbance of the membrane causes penetration of lytic component and collection of water into the cell lead to hemolysis (31).…”
Section: Discussionmentioning
confidence: 99%
“…According to them the plasma membrane disruption occurred due to disturbed lipid microenvironment and increased lipid peroxidation after the exposure to malathion. Bonarska-Kujawa et al (2014) reported echinocyte formation in RBCs after exposure to 0.1 and 0.01 mg/ ml concentration of Ribes nigrum extracts.…”
Section: Discussionmentioning
confidence: 98%
“…Uzyskane wyniki badań z zastosowaniem znaczników fluorescencyjnych pozwalają sądzić, że obecne w ekstraktach polifenole koncentrują się głównie w obszarze hydrofilowym błon erytrocytów, natomiast nie wnikają do obszaru hydrofobowego dwuwarstwy lipidowej błony. Podobne spostrzeżenia w przypadku innych ekstraktów roślinnych, przy użyciu takich samych technik badawczych, przedstawiono w pracach [3,24]. Stopień ochrony błon przed utlenieniem przez związki polifenolowe zawarte w ekstraktach określono fluorymetrycznie na podstawie stopnia gaszenia fluorescencji sondy DPH-PA przez wolne rodniki powstałe w wyniku rozpadu związku AAPH.…”
Section: Rys 1 Wartość Anizotropii (A) Sondy Dph I Uogólnionej Polaunclassified